2019
DOI: 10.1371/journal.pone.0214698
|View full text |Cite
|
Sign up to set email alerts
|

Mate choice confers direct benefits to females of Anastrepha fraterculus (Diptera: Tephritidae)

Abstract: Exposure to plant compounds and analogues of juvenile hormone (JH) increase male mating success in several species of tephritid fruit flies. Most of these species exhibit a lek mating system, characterized by active female choice. Although the pattern of enhanced male mating success is evident, few studies have investigated what benefits, if any, females gain via choice of exposed males in the lek mating system. In the South American fruit fly, Anastrepha fraterculus , females mate prefe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 58 publications
2
21
1
Order By: Relevance
“…This is in agreement with Vera et al (2013) for A. fraterculus and Flores et al (2011) for other Anastrepha species but contrasts with Bachman et al (2019), who found that copulations involving males exposed to guava volatiles lasted longer than those involving non‐exposed males. Although there is some controversy about the duration of copula as an indicator of male reproductive success in tephritid fruit flies, the evidence collected so far for A. fraterculus indicates that longer copulas correlate with lower tendency to remate and longer refractory period in the female (Abraham et al, 2011) and in higher fecundity (Bachmann et al, 2019). This high fecundity without remating would ensure high fitness to the male and, in the context of the SIT, may imply higher induced sterility in the wild population (Bachmann et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is in agreement with Vera et al (2013) for A. fraterculus and Flores et al (2011) for other Anastrepha species but contrasts with Bachman et al (2019), who found that copulations involving males exposed to guava volatiles lasted longer than those involving non‐exposed males. Although there is some controversy about the duration of copula as an indicator of male reproductive success in tephritid fruit flies, the evidence collected so far for A. fraterculus indicates that longer copulas correlate with lower tendency to remate and longer refractory period in the female (Abraham et al, 2011) and in higher fecundity (Bachmann et al, 2019). This high fecundity without remating would ensure high fitness to the male and, in the context of the SIT, may imply higher induced sterility in the wild population (Bachmann et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The essential oil from lemon largely consists of monoterpene hydrocarbons (91.9%), including limonene as the predominant compound (Ruiz et al, 2015), whereas the essential oil of S. polygama is composed mainly of monoterpene hydrocarbons and hydrocarbon sesquiterpenes with no single compound being predominant (Jofré‐Barud et al, 2014; Jofré‐Barud, 2018). Male enhancement in A. fraterculus was also achieved after exposure to guava volatiles (Vera et al, 2013; Bachmann et al, 2015, 2019), in which there is no predominant chemical group (Pino et al, 2001) and in an artificial mixture of seven compounds present in the guava volatiles, including limonene, in even proportions (Bachmann et al, 2015). Therefore, further studies are required in order to identify candidate compound(s) responsible of male enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an infected status may represent possible fitness costs, as the latency to mate decreased and the mating duration increased when flies were cured from Wolbachia . These characteristics have been proposed to be advantageous 43,44 . In the case of AfC, the absence of Wolbachia in both sexes correlates with a lower tendency to copulate, again suggesting a negative effect associated with the curing protocol.…”
Section: Discussionmentioning
confidence: 99%